In Vitro Assessment of the Antiviral Activity of Ketotifen, Indomethacin and Naproxen, Alone and in Combination, against SARS-CoV-2 - Kiani, Pantea (Viruses, 2021)
The 2019 coronavirus infectious disease (COVID-19) is caused by infection with the new severe acute respiratory syndrome coronavirus (SARS-CoV-2). Currently, the treatment options for COVID-19 are limited. The purpose of the experiments presented here was to investigate the effectiveness of ketotifen, naproxen and indomethacin, alone or in combination, in reducing SARS-CoV-2 replication. In addition, the cytotoxicity of the drugs was evaluated. The findings showed that the combination of ketotifen with indomethacin (SJP-002C) or naproxen both reduce viral yield. Compared to ketotifen alone (60% inhibition at EC(50)), an increase in percentage inhibition of SARS-CoV-2 to 79%, 83% and 93% was found when co-administered with 25, 50 and 100 μM indomethacin, respectively. Compared to ketotifen alone, an increase in percentage inhibition of SARS-CoV-2 to 68%, 68% and 92% was found when co-administered with 25, 50 and 100 μM naproxen, respectively. For both drug combinations the observations suggest an additive or synergistic effect, compared to administering the drugs alone. No cytotoxic effects were observed for the administered dosages of ketotifen, naproxen, and indomethacin. Further research is warranted to investigate the efficacy of the combination of ketotifen with indomethacin (SJP-002C) or naproxen in the treatment of SARS-CoV-2 infection in humans.